The Long-Term Variations of Phytoplankton Biomass in the Lower Nakdong River: 2000~2021 - Heejong Son; Eunyoung Jung; Goeun Kim; Seongho Jang; Byungryul An (대한환경공학회지)
Objectives Globally, the mass proliferation of phytoplankton driven by climate change has emerged as a significant societal issue. This study analyzes over two decades of long-term hydraulic, hydrological, and water quality data collected from the lower Nakdong River, along with changes in phytoplankton community biomass. The aim is to evaluate long-term trends in water quality and the ecological changes occurring in this region. Methods The monitoring site in the lower Nakdong River is Mulgeum, where samples were collected weekly from January 2000 to December 2021 for the analysis of physicochemical water quality characteristics, as well as phytoplankton abundance and species composition. The hydrological status was assessed using flow rate data from the Jin-dong (Haman) station of the Nakdong River, along with rainfall data from the Korea Meteorological Administration for eight regions influencing the lower Nakdong River. Results and Discussion Analysis of the annual average concentration changes of water quality parameters at the Mulgeum intake site in the lower Nakdong River found that water quality has generally improved since the construction period (2009-2012) of the weir. This improvement is attributed to the strengthening of T-P water quality standards for sewage treatment plant discharges in 2012, which resulted in enhanced phosphorus treatment at wastewater facilities in the river's middle and upper regions. Consequently, significant reductions were observed in the annual average concentrations of BOD, NO3-N, T-N, and T-P. Evaluating long-term changes in flow rate and rainfall, it was found that both annual average rainfall and flow rate decreased after the weir was installed, particularly from May to September when temperatures rise. Rainfall decreased by approximately 8% to 38%, while flow rate decreased by 46% to 62%. Long-term temperature changes indicated that summer temperatures increased by 0.9oC to 1.4oC, and winter temperatures rose by 1.6oC to 2.0oC, resulting in an overall annual average increase of about 1.3oC. An analysis of long-term changes in phytoplankton biomass and community composition revealed an increase in average biomass from 3,639 cells/mL before the weir was installed to 4,034 cells/mL afterward, representing an increase of about 11%. In winter, the dominance period and biomass of diatoms decreased, while in summer, the biomass and dominance period of cyanobacteria increased. Notably, in August, biomass increased approximately 7.5 times, rising from 2,009 cells/mL before the dam to 15,059 cells/mL afterward. This significant increase was identified as a key factor in the overall rise in phytoplankton biomass following the weir's installation. Conclusion Recent climate change impacts, such as rising average temperatures and shifting rainfall patterns, have become increasingly evident in South Korea. This study utilizes over 20 years of long-term data to demonstrate that, in the lower Nakdong River, there has been a gradual decline in both rainfall and flow rates, accompanied by an increase in average temperatures. Consequently, the dominance period and biomass of diatoms have decreased. In contrast, cyanobacteria, which thrive in warmer conditions, have experienced an extended dominance period into early spring and late autumn as a result of rising temperatures, leading to an overall increase in cyanobacterial biomass.